Development of a contextual teaching and learning-based teaching module on statistics to facilitate students mathematical communication skills - Amalia, Della Nur; Suanto, Elfis; Yuanita, Putri (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study was motivated by the issue of studentsâ€™ low performance in mathematical communication skills. The purpose of this development research was to produce a teaching module based on the Contextual Teaching and Learning (CTL) approach for the topic of statistics, aimed at facilitating the mathematical communication skills of seventh-grade students in junior high school. The research was conducted at SMPN 17 Pekanbaru and employed the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Validation of the teaching module was conducted by three expert validators, followed by revisions based on their suggestions and feedback. A one-on-one trial with three students was then carried out to evaluate the readability of the student worksheet within the module. After being declared valid, the module was tested on a small group of six students and a large group of 33 students to assess its practicality. The results showed that the average validation score was 90%, which falls into the â€œvery validâ€ category. Furthermore, the average student response score was 91%, indicating a â€œvery practicalâ€ category. These findings suggest that the developed teaching module is both valid and practical, and can be effectively used by teachers in the mathematics learning process.